Development of communicative competence of managers of education in the process of professional development - Luzan, L. (Problems of Engineer-Pedagogical Education, 2018)
The article considers theoretical aspects of formation of communicative competence of the manager of education in the process of professional development. While conducting current research, it was determined that communication skills occupy one of the leading positions in professional training of managers, because communication is one of the important instruments of the professional activity of a specialist in almost any sphere. Based on the analysis of scientific sources on the theoretical basis and practice of studying the issue of the formation of communicative competence of managers of education, it can be stated that there is not enough attention to the problem of developing communicative competence of heads of education in the process of their professional development. Thus, during the analysis of the definition "communicative competence", special attention was focused on its meaningful content. The article suggests methods of developing communicative competence of the head of education through the use of innovative technologies. To solve the problem, a special thematic course "Development of communicative competence" is offered, which implies using some effective techniques such as "storytelling", "art-scribing", creative work experience and others.